Impact of perioperative steroid administration in patients undergoing elective liver resection: meta-analysis. Issue 6 (20th December 2022) - Jötten, Laila; Steinkraus, Kira C; Traub, Benno; Graf, Sandra; Mihaljevic, André L; Kornmann, Marko; Michalski, Christoph W; Hüttner, Felix J
Abstract: Background: Perioperative steroid administration may improve postoperative outcomes in major abdominal surgery by reducing the systemic inflammatory response. The aim of this systematic review was to evaluate the impact of perioperative steroid administration on outcomes after elective liver resection. Methods: PubMed, Cochrane Library, and Web of Science were systematically searched for randomized clinical trials (RCTs) comparing perioperative steroid administration with placebo, standard of care, or no steroids with respect to postoperative outcomes, particularly postoperative complications. Two independent reviewers critically appraised the studies and extracted data. Meta-analyses were performed using a random-effects model with ORs calculated for dichotomous outcomes and mean differences (MDs) for continuous outcomes. Results: Ten RCTs comprising 930 patients were included. Perioperative steroid administration significantly reduced the overall postoperative complication rate (OR 0.61, 95 per cent c.i. 0.43 to 0.87; P = 0.006; I 2 = 26 per cent). No significant differences were shown for individual complications. Several postoperative laboratory parameters were positively affected, like total serum bilirubin (MD −0.46; 95 per cent c.i. −0.74 to −0.18; P = 0.001; I 2 = 80 per cent), interleukin 6 (MD −48.99; 95 per cent c.i. −60.72 to −37.27; P < 0.001; I 2 = 0 per cent) and C-reactive protein (MD −5.20; 95 per cent c.i. −7.62 to −2.77; P < 0.001; I 2 = 71 per cent). There were no signs of an increase in potential steroid-induced adverse events, namely infectious complications, thromboembolic events, or bleeding. Conclusions: Perioperative steroid administration significantly reduces the overall complication rate after elective liver resection without an increased risk of adverse effects. Abstract : In this manuscript, we performed a meta-analysis of randomized clinical trials investigating the impact of perioperative steroid administration surrounding elective liver resections. The results based on a total of 930 patients demonstrated a positive effect of steroid administration on overall postoperative complications and several laboratory parameters of liver function and inflammation.